DINAMIKA POPULASI MIKROB PADA TANAH MASAM ASAL JASINGA BOGOR DAN LEBAK BANTEN - Dewi Firnia (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
Acid mineral soils are soils that have properties such as low pH, low cation exchange capacity, low base saturation, low organic C, high Al saturation and high phosphorus fixation. The technical problem with acid soils is the low level of soil fertility which affects plant productivity. The purpose of this study was to determine the dynamics of the microb population on acid soils. The soil used was two Typic Hapludults from Neglasari Jasinga Village, Bogor and Padasuka Maja Lebak Village with different levels of Al-dd saturation. Soil microb population included total microbes, total sulfate reducing bacteria and total Acidithiobacillus ferrooxidans. Acid soils from Jasinga and Lebak have soil conditions with acidic pH, low organic C content. For acid soils from Jasinga, the highest total of microbes was at a depth of 0-35 cm and the highest total of Acidithiobacillus ferrooxidans was at a depth of 0-35 cm. Whereas for acid soils from Lebak, the highest total of microbes was at a depth of 0-15 cm and the highest total of Acidithiobacillus ferrooxidans was at a depth of 15-40 cm. There was no population of sulfate-reducing bacteria in acid soils from Jasinga and Lebak.